Constitutional amendment and public will formation: Deliberative mini-publics as a tool for consensus democracy. (11th May 2022) - Doyle, Oran; Walsh, Rachael
Abstract: Constitutionalism is in the midst of both a participatory and a deliberative turn. In this article, we explore one aspect of this turn—the use of deliberative innovations to enhance constitutional amendment processes. Ireland has been cited as almost a paradigm case for such experimentation. We assess deliberative mini-publics' potential as a tool for consensus democracy based on the experience and impact of the Irish Citizens' Assembly that made recommendations for wholesale reform of Ireland's abortion laws in 2018. We identify a "legislative-majority-plus" model for constitutional amendment deployed in most jurisdictions with master-text constitutions and on that basis, characterize constitutional amendment as an aspect of consensual, rather than competitive, democracy. Based on this understanding of the function of constitutional amendment processes, we argue that the Citizens' Assembly played a significant role in the process of public will formation. In particular, it helped to generate political and public support for a particular form of liberalization—abortion on request within the first twelve weeks—and made it easier for legislators to avoid the incentives of electoral politics and formulate an amendment proposal that attracted wide support despite intense opposition. However, we raise concerns about the normative legitimacy of that impact, based on deficiencies in the representativeness of the Assembly, arguing that in order to be a tool for will formation, rather than manipulation, in respect of constitutional amendment, deliberative mini-publics should be designed so as to enhance their representativeness.